Biology and Control of Coniophora Causing Decay and Decline in Arizona Citrus - Gilbertson, R. L. (College of Agriculture, University of Arizona (Tucson, AZ), 1996)
A field survey of mature lemon trees showed an average of 30% of trees with symptoms of brown heartwood rot caused by Coniophora sp. In vivo growth of Coniophora inoculated into branches of different types of citrus (Valencia orange, Marsh grapefruit, Orlando tangelo or Lisbon lemon) on rough lemon rootstock was significantly higher in lemon while Coniophora inoculated into Lisbon lemon wood branches on trees established on rough lemon, volkameriana, macrophylla, Cleopatra mandarin, sour orange or Troyer citrange rootstocks showed no significant differences in growth. Vegetative incompatibility trials from one mature orchard demonstrated that isolates from different trees are incompatible. In vitro fungicide trials showed that only NECTEC paste effectively reduced decay on lemon blocks 15 weeks after inoculation with Coniophora. Field fungicide trials showed that NECTEC P paste as well as the blank paste without fungicides, propiconazole at 10,000 μg /ml, imazalil at 20, 000 μg /ml or propiconazole plus imazalil in combination at 10,000 and 20,000 μg/ml, respectively, significantly inhibited the advance of fungus 7 mo. after inoculation. A second fungus isolated from brown rot in branches in younger orchards was identified as Antrodia sinuosa, a native decay fungus on conifers in Arizona.